An experimental investigation on the surface characteristics of tungsten carbide for the fine-finish die-sinking and scanning micro-EDM. (3rd April 2009) - Jahan, M.P.; Wong, Y.S.; Rahman, M.; Asad, A.B.M.A.
In this paper, a comprehensive study on the surface characteristics of tungsten carbide (WC) obtained in die-sinking and scanning micro-EDM is presented based on the crater characteristics, surface topography, average surface roughness (Ra) and peak-to-valley roughness (Rmax). The investigation shows that fine-finish micro-EDM requires minimisation of the pulse energy supplied into the gap which was found difficult to apply in die-sinking due to frequent arcing, short circuiting and unstable machining conditions. Consequently, the machined surface becomes defective due to the presence of microcracks, voids and deposition of debrises in die-sinking micro-EDM. However, the surface generated in scanning micro-EDM is less susceptible to surface defects along with lower Ra and Rmax. Investigation has also been carried out on the effect of different electrode materials on surface characteristics of WC. It was found that silver tungsten electrode provides better surface characteristics compared to tungsten and copper tungsten for the fine-finish micro-EDM of WC.